High resolution planktonic foraminifera analyses across the Paleocene/Eocene boundary at Shatsky Rise, Pacific Ocean. - M.R. Petrizzo (2006)
The latest Paleocene to earliest Eocene sediments from two Ocean Drilling Program Holes 1209B (water depth 2387 m) and 1210B (water depth 2573 m) recovered from Shatsky Rise were studied to obtain a detailed planktonic foraminifera record across the Paleocene-Eocene transition in the subtropical Pacific Ocean. At these sites the Paleocene yellowish brown calcareous ooze is overlain by a thin dark brown clay seam (~ 2 mm) at 196.42 mbsf in Hole 1209B and at 184.31 mbsf in Hole 1210B which corresponds to the base of the Paleocene-Eocene Thermal Maximum (PETM) and to the Paleocene/Eocene boundary. The PETM was an interval of rapid global warming ~55 m.y. ago associated with transformation of fauna and flora ecosystems and changes in carbon cycling. At Shatsky Rise, the onset of the PETM is marked by the abrupt onset of the negative carbon isotope excursion (CIE) which lies just below the sharp lithologic contact between more carbonate-rich ooze overlying clay-rich ooze. In the upper part of the PETM interval, the clay-rich ooze gradually becomes more carbonate rich and carbon isotope values gradually increase. A high-resolution centimeter-scale quantitative analysis of the planktonic foraminiferal assemblages was performed in order 1) to document the composition of the planktonic foraminiferal assemblages and their variations at centimeter scale, and 2) to provide a high resolution bio-chemostratigraphic correlation across the Paleocene/Eocene boundary. Quantitative analyses well document the similarity in composition of the planktonic foraminiferal assemblages between the two sites. In general, Morozovella dominates the assemblages and its maximum relative abundance is coincident with the carbon isotope excursion. Subbotinids show an opposite trend and are absent in the interval of maximum abundance of Morozovella. A decrease in abundance of about 10% in average is observed within the Acarinina group from the base to the top of the studied sections. The excursion taxa (A. sibaiyaensis, M. allisonensis, and A. ...